White Devils, Satanic Jews: The Nation of Islam From Fard to Farrakhan. Issue 2 (5th May 2020) - Norwood, Stephen H; Pollack, Eunice G
Abstract: This article explores how the American white far right—including the Christian Front, Christian Mobilizers, and Gerald L. K. Smith—helped shape the Nation of Islam's (NOI) antisemitism during the 1930s and 1940s. It also examines the strong influence of Harlem's pro-Axis Black Fuehrers on the NOI during World War II. Nation of Islam and white far-right propaganda were remarkably similar. Both embraced the Protocols of the Learned Elders of Zion, denied or minimized the Holocaust, and were virulently anti-Zionist. After elaborating on the context within which the Nation of Islam created its ideology, the article explores how the NOI, which originally identified whites, Christians and Jews as devils, adopted an almost singular emphasis on Jews as agents of Satan, the Star of David replacing the cross as the symbol of iniquity. Jews were not victims, but Blacks' major victimizers; never slaves, but dominant enslavers; not progressives, but those who impeded Blacks' advance. Instead of giving the world Hebrew Scripture, they converted it into the "Poison Book, " from the beginning crafting a "dirty religion, " which blessed the subjugation of black people, and denied God's promise to the "Real Children of Israel." These "imposter Jews" concealed that the Hebrew Bible was a prophecy about "the so-called Negroes of America"—the true "Chosen of God"—who would be in bondage for 400 years, strangers in a strange land.